Implementasi Metode Failover pada Broker Protokol MQTT Dengan ActiveMQ - Mohammad Hafidzar Rakhman; Widhi Yahya; Kasyful Amron (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Internet of Things (IoT) can be interpreted as a concept to connect "Things" or real objects in the world with the internet and sharing information. To share information between "Things" over the internet, Iot needs an ideal and efficient communication protocol in terms of resources when sending messages. One of the protocols considered to fit with IoT communication model is the Message Queuing Telemetry Transport (MQTT) protocol. In the MQTT protocol communication model, the broker has an important role in the success of the communication process that occurs. When the broker stops, the publisher and subscriber can't make the communication process and have to wait for the broker to be fixed. The solution of broker problem can be minimized by implementing failover between master and slave broker. Therefore, this study implements failover to improve the availability of services to brokers. Based on the test results, the system obtained an average downtime value of 24.3266 seconds from 5 tests. While on performance testing, the system gets an average latency value of 1.1763 seconds on the publisher side and 0.1157 seconds on the MQTT subscriber side. In packet loss testing, missing messages amount to 20 messages from 50 messages when implementing failoverl.